Impression management in daily life: an experience sampling test for the expression of impression management as interpersonally oriented self-control - Uziel, Liad; Schmidt-Barad, Tomer (Frontiers in Psychology, 2023)
Impression management (IM) scales (often called lie or social desirability scales) have long been applied as validity scales in assessment processes. Recent developments have indicated that these scales measure a substantive personality predisposition and not response bias, but the nature of the disposition is disputable. According to the 'interpersonally oriented self-control' approach, IM is associated with high self-control exerted mainly in public social contexts to facilitate adaptation. Supported in laboratory settings, this approach has not been tested in real-life dynamics. In the present experience sampling study, participants reported 3 times a day (10 days) about their social condition (alone/'with others') and their level of self-control. Results revealed that IM was associated with stronger self-control when with other people than when alone. Comparable reactions to public social context were not found for self-deception enhancement, trait self-control, or agreeableness, marking this a unique aspect of IM. The findings further stress the need to reconsider the use of IM scales for validity purposes in assessment processes.